Modeling Canal Blocking with Endemic Vegetation in Jatimulyo Village - Rike Puspitasari Tamin; Fazriyas; Richard R.P. Napitupulu; Jenny Rumondang; Andita Minda Mora (Altifani Journal: International Journal of Community Engagement, 2024)
Peatland fires in Jambi Province are recurrent, consuming above-ground vegetation and causing large-scale ecosystem damage. Peat ecosystem restoration efforts must begin with rewetting through the construction of canal blocks to inhibit water loss and keep peat soil moist during the dry season. The construction of canal blocks in peatlands has been carried out, including in Jatimulyo Village, Dendang District, East Tanjung Jabung Regency, Jambi Province. Semi-permanent canal bulkhead structures often break down if the water discharge from upstream is very large so that the bulkhead does not last long. The purpose of this activity was to design a model for strengthening canal bulkheads using endemic vegetation species including pulai, jelutong, and gelam planted on the bulkhead body structure. Endemic vegetation planting was carried out in four canals by planting pulai, gelam, and jelutong seedlings. Each canal was planted with a distance of 50x 50 cm so that there were approximately 74 seedlings planted in each canal bulkhead body. This PKM activity is expected to have an ecological impact on peatlands, especially in Jatimulyo Village, both in the short term to strengthen the canal structure and in the long term to maintain a wet state on peatlands.